Transcriptome Complexity and Riboregulation in the Human Pathogen Helicobacter pylori - Sharma, Cynthia M.; Pernitzsch, Sandy R. (Frontiers in Cellular and Infection Microbiology, 2012)
The Gram-negative Epsilonproteobacterium Helicobacter pylori is considered as one of the major human pathogens and many studies have focused on its virulence mechanisms as well as genomic diversity. In contrast, only very little is known about post-transcriptional regulation and small regulatory RNAs (sRNAs) in this spiral-shaped microaerophilic bacterium. Considering the absence of the common RNA chaperone Hfq, which is a key-player in post-transcriptional regulation in enterobacteria, H. pylori was even regarded as an organism without riboregulation. However, analysis of the H. pylori primary transcriptome using RNA-seq revealed a very complex transcriptional output from its small genome. Furthermore, the identification of a wealth of sRNAs as well as massive antisense transcription indicates that H. pylori uses riboregulation for its gene expression control. The ongoing functional characterization of sRNAs along with the identification of associated RNA binding proteins will help to understand their potential roles in Helicobacter virulence and stress response. Moreover, research on riboregulation in H. pylori will provide new insights into its virulence mechanisms and will also help to shed light on post-transcriptional regulation in other Epsilonproteobacteria, including widespread and emerging pathogens such as Campylobacter.